ACCOUNTING TREATMENT OF THE BOND SINKING FUND AND RESERVE. - Atkinson, Sterling K. (The Accounting Review, 1935)
Abstract The purpose of this article is to review briefly the accounting treatment of the bond sinking fund and its reserve in their relation to current corporate financial policy. The writer does not intend to discuss the bookkeeping technique involved as such. Most studies on accounting theory review, at least briefly, the entries necessary to record the creation of the fund and the accompanying reservation of surplus. It is intended here, rather, to raise certain questions concerning the background of financial policy and procedure out of which this technique arises. The author wishes to emphasize two points. First, a study of accounting theory necessarily is related to business practice. Students draw inferences concerning it even though they are directly concerned with theoretical concepts and with problems of recording technique. Second, the study of corporation accounting respecting dividend policy has over-emphasized the surplus approach and consequently has resulted in students acquiring a too legal viewpoint.